A biomechanical comparison of posterior fixation approaches in lumbar fusion using computed tomography based lumbosacral spine modelling - Ramakrishna, Vivek As; Chamoli, Uphar; Larosa, Alessandro G; Mukhopadhyay, Subhas C; Gangadhara Prusty, B; Diwan, Ashish D (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2023)
Extreme lateral interbody fusion (XLIF) may be performed with a standalone interbody cage, or with the addition of unilateral or bilateral pedicle screws; however, decisions regarding supplemental fixation are predominantly based on clinical indicators. This study examines the impact of posterior supplemental fixation on facet micromotions, cage loads and load-patterns at adjacent levels in a L4-L5 XLIF at early and late fusion stages. CT data from an asymptomatic subject were segmented into anatomical regions and digitally stitched into a surface mesh of the lumbosacral spine (L1-S1). The interbody cage and posterior instrumentation (unilateral and bilateral) were inserted at L4-L5. The volumetric mesh was imported into finite element software for pre-processing, running nonlinear static solves and post-processing. Loads and micromotions at the index-level facets reduced commensurately with the extent of posterior fixation accompanying the XLIF, while load-pattern changes observed at adjacent facets may be anatomically dependent. In flexion at partial fusion, compressive stress on the cage reduced by 54% and 72% in unilateral and bilateral models respectively; in extension the reductions were 58% and 75% compared to standalone XLIF. A similar pattern was observed at full fusion. Unilateral fixation provided similar stability compared to bilateral, however there was a reduction in cage stress-risers with the bilateral instrumentation. No changes were found at adjacent discs. Posterior supplemental fixation alters biomechanics at the index and adjacent levels in a manner that warrants consideration alongside clinical information. Unilateral instrumentation is a more efficient option where the stability requirements and subsidence risk are not excessive.